A utilização de resíduos urbanos na geração de energia elétrica na cidade de São Carlos - Andrade, Lívia Sanches (Universidade Federal de São Carlos, 2023)
This project aimed to determine the viability of installing an Energy Recovery Unit in São Carlos. To fundament the thesis, the impact of the current pattern of waste disposal was analyzed, from social to financial aspects, such as its long-term fit within the growing sustainability aspect. Once the need for alternative routes was identified, a comparison was made between the models of energy use by thermal degradation and their application in other countries. Since this set of processes occurs only in favorable burning conditions, a detail of the raw material was made based on information provided by the Municipal Plan of Integrated Waste Management, the Energy Research Company, and other reliable studies. Through this, the calorific power values and the energy potential generated for the total amount of municipal solid waste (US) produced per day in the city were obtained, to obtain the first green light towards the project's goal. Following the financial analysis, cash flow projections were made taking as reference the initial investments and operating conditions from the same type of industry in Barueri, which will be inaugurated in 2026, along with expenses and profits reported in other functional plants. Through the calculations of present value, initial rate of return, and payback time, twelve scenarios were created with variations of energy prices, carbon credit, and payment of loans to approximate the simulation of reality. Finally, the benefits of this sustainable process have been proven, creating solid theses to further defend the intelligent garbage disposal. The exponents of this discussion were also the significant reduction of its volume, the generation of clean energy in place of non-renewable sources, and the social and environmental protection guaranteed with the portion of hazardous waste used in the burning.
The use of urban waste in the generation of electricity in the city of São Carlos
Keywords: Resíduos sólidos urbanos; Geração de energia; Sustentabilidade; Municipal solid waste; Power generation; Sustainability; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA